WATERMELON PEEL EXTRACT AS GREEN CORROSION INHIBITOR FOR ST-37 CARBON STEEL IN SEAWATER - Sri Teguh Priharti; Umar Kalmar Nizar; Rita Sundari; Sri Benti Etika; Budhi Oktavia; Ananda Putra; Rini Anggraini (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2021)
Corrosion engineering has taken great interest in many industries that required high cost management to overcome the serious problems. This work has investigated the role of watermelon peel extract as green inhibitor to protect carbon steel in seawater. This investigation has studied the corrosion rate and inhibition efficiency applying weight loss method.  The laboratory result shows the optimum inhibition efficiency found to be 71.64% at 5% inhibitor concentration in 100 ml seawater at room temperature. The effects of temperature and immersion time on inhibition efficiency have also been examined.  This study has used Arrhenius equation based on activation energy to determine type of adsorption encountered with corrosion process. The result shows a chemical adsorption justified by its high adsorption heat and strengthened by FTIR and UV-Vis examinations. The phytochemical examination of watermelon peel extract gives positive response to flavonoid, alkaloid, and saponin. The finding is useful for many industries encountered with carbon steel corrosion in corrosive medium using green inhibitor.